The implementation of performance analysis and feedback within Olympic sport: The performance analyst's perspective - Nicholls, S. B.; James, N.; Bryant, E.; Wells, J. (International Journal of Sports Science & Coaching, 2019)
The study considered performance analysis and feedback from the perspective of the performance analyst through the investigation of the `what`, `how` and `when` of practice within a selection of Olympic sports. Twenty-three performance analysts (experience 6.4 ± 4.1 years) engaged in a structured interview (85 ± 15 min) regarding their processes within applied practice. Likert scales (All the time, Often, Sometimes, Rarely and Never) were used to facilitate cross-sport and environment comparison. The performance analysts highlighted the experience of their coaches as the most prominent feature influencing analysis direction, and time had the greatest impact upon feedback provision. The main analysis techniques used were video, profiling and performance reports. Feedback was delivered primarily either, (1) < 1-h post-performance within sessions lasting < 10-min or (2) the following day within sessions lasting 25 + min. Video feedback was usually coach led; however, data delivery was more evenly distributed between coach and analyst. Very similar processes across the participants were identified, despite a wide variety of sports and participant experience levels. The findings have begun to illustrate practice within elite sport whilst highlighting the importance and need for further practitioner-based investigation regarding the use of performance analysis and feedback within applied contexts.